2020
DOI: 10.3892/mmr.2020.11337
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of catalpol on mitochondria of hepatocytes in cholestatic liver injury

Abstract: cholestasis, which is caused by the obstruction of bile flow, can lead to rapid organ injury, cell apoptosis and necrosis of hepatocytes, and may eventually develop into fibrosis and cirrhosis. Oxidative stress and mitochondrial dysfunction are the key pathogenic signs of hepatic cholestasis. Catalpol has pharmacological activities, including antioxidative and anti-inflammatory effects, and may relieve mitochondrial damage and restore mitochondrial membrane potential. However, the potential roles and mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…ΔΨm in AD cells was decreased while ΔΨm was increased after catalpol treatment. Catalpol reduces ROS level and enhanced mitochondrial ΔΨm in mice with liver injury, and reduces mitochondrial damage in ischemic injury (Cai et al, 2018;Gao et al, 2020). These results demonstrated that catalpol reduced Aβ 1−42 -induced mitochondrial damage and ROS generation.…”
Section: Discussionmentioning
confidence: 69%
“…ΔΨm in AD cells was decreased while ΔΨm was increased after catalpol treatment. Catalpol reduces ROS level and enhanced mitochondrial ΔΨm in mice with liver injury, and reduces mitochondrial damage in ischemic injury (Cai et al, 2018;Gao et al, 2020). These results demonstrated that catalpol reduced Aβ 1−42 -induced mitochondrial damage and ROS generation.…”
Section: Discussionmentioning
confidence: 69%
“… 45 Catalpol improves the mitochondrial membrane potential and regulates inflammatory cytokines and the expression of apoptotic proteins through antioxidant effects and protects the liver from cholestasis-mediated injury. 46 GA inhibits lipid accumulation, apoptosis and inflammation in hepatocytes by activating AMPK. 47 CA alleviates oxidative stress in the liver by scavenging mitochondria and intracellular ROS, inhibits steatosis, hepatocyte apoptosis and liver fibrosis, and improves alcoholic liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Catalpol (CTP), an iridoid glycoside extracted from traditional Chinese medicine Rehmannia glutinosa , has been reported to have antitumor (Zhu et al 2017), antidiabetic (Zhu et al 2016; Bao et al 2016), anti‐inflammatory (Park 2016), anti‐asthma (Chen et al 2017), antioxidant, and other remarkable pharmacological effects. CTP also has a palliative effect on hepatic fibrosis and has been shown to alleviate CCl 4 ‐induced hepatic fibrosis in rats and cholestasis‐induced mouse liver injury (Liu et al 2018; Gao et al 2020). However, whether CTP could alleviate mouse hepatic fibrosis and the underlying mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%